2004
DOI: 10.1007/978-3-540-24730-2_15
|View full text |Cite
|
Sign up to set email alerts
|

A Tool for Checking ANSI-C Programs

Abstract: Abstract. We present a tool for the formal verification of ANSI-C programs using Bounded Model Checking (BMC). The emphasis is on usability: the tool supports almost all ANSI-C language features, including pointer constructs, dynamic memory allocation, recursion, and the float and double data types. From the perspective of the user, the verification is highly automated: the only input required is the BMC bound. The tool is integrated into a graphical user interface. This is essential for presenting long counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
838
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,045 publications
(843 citation statements)
references
References 8 publications
(5 reference statements)
1
838
0
4
Order By: Relevance
“…Our symbolic encoding for detecting atomicity violations is related to, but is different from, the SSA-based SAT encoding [15], which is popular for sequential programs. Our analysis differs from the context-bounded analysis in [25,26,16] since they a priori fix the number of context switches in order to reduce concurrent programs to sequential programs.…”
Section: Related Workmentioning
confidence: 99%
“…Our symbolic encoding for detecting atomicity violations is related to, but is different from, the SSA-based SAT encoding [15], which is popular for sequential programs. Our analysis differs from the context-bounded analysis in [25,26,16] since they a priori fix the number of context switches in order to reduce concurrent programs to sequential programs.…”
Section: Related Workmentioning
confidence: 99%
“…As the CWE gathers almost any kind of error, which is observable in a computer based environment, we do by far not match all error classes, but only show the most relevant ones for static software analysis. The result of these tests is shown in Table 1, where we have compared MEMICS with two analysis tools, CBMC [CKL04] and LLBMC [SFM10], which are also operating based on BMC. With this results we have shown that our tool is already able to identify a lot of runtime errors, as well common sequential as difficult concurrent ones.…”
Section: Resultsmentioning
confidence: 99%
“…The first module parses the input program, the second carries out the preprocessing, the third builds the quantifier-free formula, and the fourth module solves the formula according to the user options by invoking CVC Lite. 3 The latter module also builds and prints the error trace whenever a counterexample is returned by CVC Lite.…”
Section: Resultsmentioning
confidence: 99%